2014
DOI: 10.1089/ars.2013.5517
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Stretch-Induced Activation of ROS/RNS Signaling in Striated Muscle

Abstract: Significance: Mechanical activation of reactive oxygen species (ROS) and reactive nitrogen species (RNS) occurs in striated muscle and affects Ca 2+ signaling and contractile function. ROS/RNS signaling is tightly controlled, spatially compartmentalized, and source specific. Recent Advances: Here, we review the evidence that within the contracting myocyte, the trans-membrane protein NADPH oxidase 2 (Nox2) is the primary source of ROS generated during contraction. We also review a newly characterized signaling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
75
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(78 citation statements)
references
References 82 publications
3
75
0
Order By: Relevance
“…The origin of ROS production remains unclear during VIDD although recent studies rather consider that mitochondria represent the main source of ROS (10). Recent studies have identified a new transduction pathway in which the microtubule network acts as a mechano-transduction element that activates NADPHoxidase 2 (Nox2)-dependent ROS generation during mechanical stretch (36). Such pathway could therefore contribute to this primary ROS production.…”
Section: Discussionmentioning
confidence: 99%
“…The origin of ROS production remains unclear during VIDD although recent studies rather consider that mitochondria represent the main source of ROS (10). Recent studies have identified a new transduction pathway in which the microtubule network acts as a mechano-transduction element that activates NADPHoxidase 2 (Nox2)-dependent ROS generation during mechanical stretch (36). Such pathway could therefore contribute to this primary ROS production.…”
Section: Discussionmentioning
confidence: 99%
“…NOX4 was also found in the mitochondria, more specifically in the inner mitochondrial membranes [8]. NOX4 is constitutively active and does not require association with regulatory subunits, being mainly regulated by its expression levels [5, 8, 9]. NOX2 can be activated by specific agonists, such as angiotensin II, growth factors, and cytokines, as well as mechanical stress/contraction, which induce the association of regulatory subunits (p47phox, p67phox, p40phox, and Rac1) and the activation of this enzyme [9].…”
Section: Introductionmentioning
confidence: 99%
“…3, [133135]). Another possibility is that Nox-derived ROS cause sarcoplasmic reticulum Ca 2+ leak [89, 140] or extracellular Ca 2+ entry into the sarcoplasm through ‘transient receptor potential’ channels [131, 141, 142]. These processes heighten cytosolic Ca 2+ concentration.…”
Section: Redox Cross-talkmentioning
confidence: 99%
“…This phenomenon has been termed X-ROS and was reviewed in detail by Ward et al [141]. The working hypothesis is that Rac1 is associated with microtubules and activates pre-assembled Nox2 complexes upon mechanical perturbation [141]. Stretching causes pronounced increases in ROS production by muscle [25, 176, 180].…”
Section: Nox and Skeletal Muscle Biology In Health And Diseasementioning
confidence: 99%